Analysis Of Factors Associated With Exclusive Breastfeeding Among Infants Of Working Mothers In The Plantation Of Sri Bandung Village, Ogan Ilir District - Oktari, Vivi; Sunarsih, Elvi; Muntaha, Amar; Mangunsong, Sonlimar (PT. Hafasy Dwi Nawasena, 2024)
Exclusive breastfeeding for 6 months is an important health behavior to reduce infant mortality and support cognitive development by preventing infection. This shows the importance of exclusive breastfeeding practices in maintaining the health of babies and supporting their growth and development. This research was conducted with the aim of identifying an analysis of factors related to exclusive breastfeeding for babies from mothers who work in the Sri Bandung Village Plantation, Ogan Ilir Regency. The method used is an analytical study with a cross sectional approach. The research involved 33 respondents who worked on plantations in Sri Bandung Village, Ogan Ilir Regency. In this study, an analysis of factors related to exclusive breastfeeding for babies from mothers who work on plantations was carried out. This research method provides an overview of the relationship between the variables studied at a certain time. The results of the study showed that there was no significant relationship between several variables such as age, early initiation of breastfeeding, knowledge, and exposure to formula milk promotion with exclusive breastfeeding for babies from mothers who worked on plantations in Sri Bandung Village, Ogan Ilir Regency. However, these results indicate that there are other factors that also contribute to the practice of exclusive breastfeeding that need further research.